The coherence of adolescent’s emotional and behavioral problems and changes over three years: Age and gender differences - Malinauskienė, Oksana; Žukauskienė, Rita (Psichologija, 2007)
Adolescent emotional and behavioural problems probably eventuate through a variety of developmental pathways and exposure to several risk factors. Several salient influences and concomitants associated with an increased risk of adolescent emotional and behavioural problems have been previously documented, including being female or male, low parental support, and substance use. The research focuses on adolescence as an important developmental period for understanding its emotional and behavioural problems and their correlations. To date, there have been few longitudinal studies on the possible structural relationships among emotional and behavioural problems in adolescent samples. The purpose of the present study was to gain a more comprehensive understanding of the longitudinal relationships among these factors and to demonstrate how they differ by sex. This study expands upon previous studies and upon the current body of literature by utilizing a longitudinal design and considering the stability and change of emotional and behavioural problems during adolescence. The longitudinal analyses contribute through clarifying ambiguities in previous findings of concurrent relations and longitudinal trends of emotional and behavioural problems. Finally, this investigation focused on a community sample, to enable a better generalization of the results to other community samples of troubled youth. Using a longitudinal sample, this study aims to analyze (1) how emotional and behavioural problems are associated with each other in adolescence, in different age groups, (2) how emotional and behavioural problems change over a three-year period, and (3) how these developmental tendencies are related to child’s gender. The sample consisted of 317 adolescents: 174 girls (55%) and 143 boys (45%). Emotional and behavioural problems were assessed at ages 14, 15 and 16 by the Youth Self Report (YSR) completed by the children. The study found that emotional and behavioural problems are associated: in all age groups, a coherence among anxiety/depression, somatic complaints, withdrawal, aggression and delinquency was apparent. Evidence suggests that emotional and behavioural problems, except withdrawal and delinquency, are relatively stable, however, the intensity of problems changes over time. Gender differences were apparent: in all age groups, girls scored higher than boys on anxiety/depression and somatic complaints, while boys scored higher than girls on the delinquency scale. The interactions between gender*age for anxiety/depression, somatic complaints, withdrawal, aggression and delinquency were not significant, implying that for both boys and girls these problems over a three-year period remained on the same level.